A cross‐sectional community‐based observational study of asymptomatic SARS‐CoV‐2 prevalence in the greater Indianapolis area. Issue 11 (2nd July 2020) - Meyers, Kristin J.; Jones, Meghan E.; Goetz, Iris A.; Botros, Fady T.; Knorr, Jack; Manner, David H.; Woodward, Brad
Abstract: The Asymptomatic novel CORonavirus iNfection (ACORN) study was designed to investigate the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in the asymptomatic adult population of the Indianapolis metropolitan area, to follow individuals testing positive for the development of symptoms, and to understand duration of positive test results. ACORN is a cross‐sectional community‐based observational study of adult residents presenting asymptomatic for COVID‐like illness, defined as the self‐reported absence of the following three symptoms in the last 7 days: fever (≥100°F), new‐onset or worsening cough, and new‐onset or worsening shortness of breath. SARS‐CoV‐2 infection was determined by real‐time reverse transcription‐polymerase chain reaction in nasopharyngeal swab samples. SARS‐CoV‐2 infection prevalence was expressed as a point estimate with 95% confidence interval (CI). Test results are reported for 2953 participants who enrolled and underwent nasopharyngeal swab testing between 7 April 2020 and 16 May 2020. Among tested participants, 91 (3.1%; 95% CI: 2.5%‐3.7%) were positive for SARS‐CoV‐2. Overall, baseline characteristics, medical history, and infection risk factors were comparable between SARS‐CoV‐2 positive and negative participants. Within the ongoing 14‐day follow‐up period for positive participants, 58 (71.6%) of 81 assessed participants remained asymptomatic while others (n = 23, 28.4%) reported one or more symptoms. Indiana had "Stay‐at‐Home" orders in place during nearly the entire test period reported here, yet 3.1% of asymptomatic participants tested positive for SARS‐CoV‐2. These results indicate screening questions had limited predictive utility for testing in an asymptomatic population and suggest broader testing strategies are needed. Importantly, these findings underscore that more research is needed to understand the viral transmission and the role asymptomatic and presymptomatic individuals play in this global pandemic.